A direct torque control of induction motor using V/f PWM technique - Y. Kumsuwan (2018)
This paper presents a new DTC for induction motor drive system using V/f PWM technique. This technique is based on the error of torque and magnitude of the stator flux to generate reference stator voltage and frequency fed to motor. The stator flux vector angle is not used to calculate stator voltage. Thus, this is a simple and easy to control by using the carrier-based space vector pulse width modulation instead of hysteresis controllers and does not require a look-up table. The simulation results in Matlab/Simulink is presented prior to hardware implementation the DTC using V/f PWM technique with the new scheme. © 2005 IEEE.